A Review On Palm Oil-based Nanofluids As A Future Resource For Green Transformer - Nur S. Suhaimi; Mohd T. Ishak; Abdul R. A. Rahman; Muhammad F. Md. Din; Mohd Z. Z. Abidin; Azhar K. Khairi (IEEE, 2024)
IEEE Access Volume 10 Page (103563-103586)